Contribuição ao conhecimento fitoquímico de Krameria tomentosa A.St.-Hil. (krameriaceae) - Andrade, Rodrigo Silva de (2020)
The Krameriaceae family is composed of a single genus, Krameria Loef., which has 18 species distributed mainly in tropical regions of North, Central and South America. Among these, Krameria tomentosa A. St.-Hil, popularly known as ―carrapicho‖ being widely in northeastern Brazil, and used in folk medicine to treat diarrhea and ulcers, in adidtion to preventing of gingival and vaginal hemorrhages. Previous studies with this species have shown the presence of neo-lignans of pharmacological interest. Furthermore, K. tomentosa has already been evaluated for its toxicity, and the isolated norneolignan of this species, the 2-(2'-hydroxy-4',6'-dimethoxyphenyl)-5-(E)-propenylbenzofuran had an vasorelaxant effect in the rat aorta, highlighting this species as promising for the continuity of its studies. Therefore, in this work, it was decided to continue the study of K. tomentosa, in order to expand its phytochemical knowledge and enable the realization of pharmacological studies of the substances obtained. For this, the roots of K. tomentosa were collected in the municipality of Santa Rita-PB, then were sequentially dried and pulverized and subjected to extraction processes, partition and chromatography techniques to isolate their chemical constituents. The isolated substances were identified by spectroscopic methods such as infrared, 1H and 13C uni and bidimensional nuclear magnetic resonance, mass spectrometry and by comparisons with the literature. The present study resulted in the isolation and identification of eight substances and two mixtures. Being, a mixture of epimers from multifidol glucoside and a mixture of (-)-syringaresinol and p-hydroxy-benzaldehyde that were first reported in the Krameriaceae family, in addition to theses, the compounds (2S,3S,4R,16E)-2-[(2'R)-2'-hydroxynonadecanoylamino]-heneicosadec-16-en-1,3,4-triol and 2,4-bis(2-phenylpropan-2-yl)phenol, were isolated for the first time in the Krameriaceae family; and still the neo-lignan (2R,3R)-2,3-dihydro-2-(4-hydroxy-3-methoxyphenyl)-3-methyl-(E)-propenylbenzofuran and the cyclic polymer kramecine, were first reported in this species. In addition, ottomentosa, sobraline, 2-(2'-hydroxy-4',6'-dimethoxyphenyl)-5-(E)-propenylbenzofuran and 2-(2',4'-dihydroxyphenyl)-5-(E)-propenylbenzofuran were re-isolated in this species. Thereby, this work contributed to the chemotaxonomic knowledge of the Krameriaceae family and to the species Krameria tomentosa, in addition to providing substances for carrying out studies about their pharmacological activities